Hubungan Dukungan Sosial dengan Body Image pada Perempuan di Media Sosial - Zahara Della Adexy Bayu; Ade Herdian Putra (International Journal of Applied Counseling and Social Sciences, 2026)
Social media exposes female college students to idealized appearance standards that can shape how they evaluate their own bodies. Social support is assumed to buffer this pressure, yet its relationship with body image among female students remains underexplored, particularly in the context of social media use. This study examined the relationship between social support and body image among female college students who use social media. A quantitative correlational design was applied to 394 female students at Universitas Negeri Padang, selected through proportional random sampling from a population of 23,317 students, using validated scales. Data were analyzed with Spearman’s rho due to a non-normal distribution. Results showed that social support was high (75.35%) and body image was moderate (63.01%), with a positive but very weak significant correlation between the two variables (r = .131; p = .009). Social support therefore contributes only marginally to body image.